Antiviral efficacy of homœopathic drugs against animal viruses - Singh, L.M.; Gupta, Girish (British Homeopathic Journal, 1985)
The antiviral effect of homœopathic drugs against two animal viruses, Chicken Embryo Virus (CEV) of fowls and Simliki Forest Virus (SFV), causing encephalitis and death in mice were investigated. In all 10 drugs in 33 potencies were tested against CEV and 8 drugs in 26 potencies showed varying degree of virus inhibition. The drugs that caused 100% inhibition of CEV were Typhoidinum 200, Hydrophobinum 1000, Tuberculinum 1000, Nux vomica 200, and Malandrinum 1000. Of the drugs tested in 11 potencies against SFV, none were found effective in either preventing disease or death of mice infected with this virus.